Numerical Study of Hall Current Effect on MHD Nanofluid with Inclined Plates in the Presence of Brownian motion and Thermophoresis - G. Gangadhar, K. Sharath Babu, V. Srinivasa Kumar (Mathematical Statistician and Engineering Applications, 2023)
This research article deals with the impact of Hall current on an electrically conducting nanofluid flow past a continuously stretching surface with heat generation/absorption has been explored. Transverse magnetic field with the assumption of small Reynolds number is implemented vertically. Appropriate similarity transformations are utilized to transform the governing partial differential equations into the non-linear ordinary differential equations. Numerical solutions for the dimensionless velocity, temperature and nanoparticle concentration are computed with the help of the shooting method. The impact of each of the Hall current parameter, Brownian motion parameter, Prandtl number, thermophoresis parameter and magnetic parameter on velocity, concentration and temperature, is discussed through graphs. The skin friction coefficient along the x? and z? directions, the local Nusselt number and the Sherwood number are calculated numerically to look into the inside behavior of the emerging parameters.